Applied Pharmaceutical Analysis India 2014 conference report. (July 2014) - Kole, Prashant; Barot, Deepak; Kotecha, Jignesh; Raina, Vijay; Rao, Mukkavilli; Yadav, Manish
Applied Pharmaceutical Analysis (APA) India 23–26 February 2014, Ahmedabad, India The fifth Applied Pharmaceutical Analysis (APA) India meeting was held in February 2014 at Hyatt Ahmedabad, India. With the theme of 'The Science of Measurement: Current status and Future trends in Bioanalysis, Biotransformation and Drug Discovery Platforms', the conference was attended by over 160 delegates. The agenda comprised advanced and relevant research topics in the key areas of bioanalysis and drug metabolism. APA India 2014 provided a unique platform for networking and professional linking to participants, innovators and policy-makers. As part of the global research community, APA India continues to grow and receive considerable attention from the drug discovery and development community of India.